2009
DOI: 10.1097/bcr.0b013e3181a28e13
|View full text |Cite
|
Sign up to set email alerts
|

Activated Nuclear Factor Kappa B and Airway Inflammation After Smoke Inhalation and Burn Injury in Sheep

Abstract: In a recent study, we have shown a rapid inflammatory cell influx across the glandular epithelium and strong proinflammatory cytokine expression at 4 hours after inhalation injury. Studies have demonstrated a significant role of nuclear factor kappa B in proinflammatory cytokine gene transcription. This study examines the acute airway inflammatory response and immunohistochemical detection of p65, a marker of nuclear factor kappa B activation, in sheep after smoke inhalation and burn injury. Pulmonary tissue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
2
18
0
1
Order By: Relevance
“…All of these factors play an important role in lung inflammatory injury. Cox RA et al [28] demonstrated that smoke inhalation and burn-induced lung injury was involved with the activation of NF-κB. In our present work, the results exhibited that treatment with UTI inhibited smoke inhalationinduced increase in NF-κB p65 activity and decrease in IκB-β in smoke-challenged rats.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…All of these factors play an important role in lung inflammatory injury. Cox RA et al [28] demonstrated that smoke inhalation and burn-induced lung injury was involved with the activation of NF-κB. In our present work, the results exhibited that treatment with UTI inhibited smoke inhalationinduced increase in NF-κB p65 activity and decrease in IκB-β in smoke-challenged rats.…”
Section: Discussionsupporting
confidence: 61%
“…However, UTI administration dramatically inhibited the overproduction of IL-1β, IL-6 and IL-8. JNK and NF-κB have been proved to involve with the pathogenesis of smoke inhalation-induced lung injury [27,28]. Expression of NF-κB p65 in nucleus reflects the activation of NF-κB [29].…”
Section: Uti Inhibited Smoke Inhalation-induced Pulmonary Inflammationmentioning
confidence: 99%
“…54 These mediators reach the lung through the bronchial circulation, triggering pulmonary inflammation, dysfunction, 55 and recruiting neutrophils, which play an important role in the pathogenesis of smoke inhalation injury. 56,57 Our results indicate that progression of this inflammatory process from the airway to the pulmonary parenchyma with ensuing cell metabolic activation and associated ventilation-perfusion mismatch occur earlier than it would be inferred from previous studies showing that 24 to 48 h were needed to observe reduced PaO 2 /FiO 2 , 12,13 neutrophil infiltration 14 and NF-kB activation 15 in bronchioles and pulmonary parenchyma. This finding is important because it implies that the therapeutic window for antiinflammatory therapies 10,58 might be soon after smoke inhalation and most likely before classical manifestations of ALI appear.…”
Section: Discussionsupporting
confidence: 45%
“…An experimental study demonstrated that lung lymph flow is increased at 4 h after smoke inhalation, 11 suggesting that initial signs of pulmonary inflammation may appear earlier than the increase in shunt fraction, 12 decrease in PaO 2 /FiO 2 , 12,13 neutrophil infiltration 14 and activation of inflammatory pathways 15 that occur in the lungs of animals at 24 to 48 h after smoke inhalation. Increased uptake of glucose by pulmonary inflammatory cells is also a sign of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Segue-se um período de intensa reação inflamatória com redução da produção do surfactante pulmonar, colapso e atelectasias. O aumento da permeabilidade capilar amplia a lesão das vias aéreas e o edema pulmonar (9).…”
unclassified